Effect of Aluminum Doping on the Optical, Electrical, and Gas Sensing Properties of ZnO Thin Films - Samundra Marasini; Sumitra Pandey; Rishi Ram Ghimire; Pramod Subedi (Progress in Physics of Applied Materials)
The study explored the effects of aluminum doping on the optical and electrical properties of ZnO thin films, along with their gas sensing capabilities, specifically in response to blood serum. Thin films were prepared using a spin-coating method, followed by annealing at 500°C, with varying Al doping concentrations (0%, 0.5%, 1%, 1.5%, 2%, and 2.5%). The results showed that higher Al doping improved the transmittance, likely due to enhanced crystallinity and the Burstein-Moss effect, with 2.5% Al-doped ZnO exhibiting the highest transmittance of around 85%. The refractive index and extinction coefficient analyses indicated a decrease in light absorption and scattering at higher doping levels, reflecting improved film quality. The real and imaginary parts of the dielectric constant also varied with doping, with 0.5% Al-doped ZnO showing the highest real part, suggesting better dielectric properties. The optical band gap of Al-doped ZnO films decreased with increasing Al concentration, consistent with previous studies, indicating potential improvements in electrical conductivity. The electrical properties, particularly I-V characteristics, revealed that higher Al doping decreased conductivity, likely due to increased charge carrier scattering. Gas sensing experiments demonstrated that 2% Al-doped ZnO exhibited higher sensitivity to blood serum, while resistance varied with time and serum volume, highlighting the dynamic interaction between the ZnO films and their environment. The study's findings suggest that Al doping enhances the optical and sensing properties of ZnO thin films, with an optimal doping concentration around 2% for maximum sensitivity.